Childcare and work: joint decisions among women in poor neighborhoods of Guatemala City - Hallman, Kelly; Quisumbing, Agnes R.; Ruel, Marie T.; de la Briere, Benedicte (International Food Policy Research Institute, 2003)
This study investigates the effects of childcare on work and earnings of mothers in poor neighborhoods of Guatemala City. Recognizing that mothe'rs work status may depend on the availability of childcare, decisions to participate in the labor force and to use formal day care are modeled to allow for the possibility that they may be jointly determined. We then explore the impact of childcare prices on mothers' earnings, conditional on her decision to work. Also explored is whether a mother's "status" within her household (as measured by the value of the assets she brought to her marriage) influences her entry into the labor force.....Our results indicate that participation in the labor market and use of formal day care are, in fact, joint decisions for mothers. Life cycle and household demographic factors have important effects on both decisions. Maternal education is an important determinant of utilization of formal day care, but does not have large effects on whether she works for pay or not. Higher household wealth reduces her chances of working, presumably via an income effect. However, the value of assets she brought to her marriage increases the likelihood of her working.